Prevalence of Argulus indicus, histopathology and hematological properties of infected wild fish in Lake Towuti, Indonesia - Amriana Amriana; Kesuma D. Sari; Sriwulan Sriwulan; Hilal Anshary (Society for Indonesian Biodiversity, 2021)
Abstract. Amriana, Sari DK, Sriwulan, Anshary H. 2021. Prevalence of Argulus indicus, histopathology and hematological properties of infected wild fish in Lake Towuti, Indonesia. Biodiversitas 22: 3578-3584. Parasites are disease agents that can threaten the health and survival of wild fish as individuals and at a population level. This study aimed to improve knowledge on the prevalence of Argulus indicus, infestation rates and the pathological effects of parasite infestation on hosts as well as hematological properties of infected fish. This study can inform future studies on the prevention and control of the cases of Argulus indicus infestation. Fish from Lake Towuti (20 45? 0? S, 1210 30? 0? E) were caught from February to May 2019 using traps and gill nets. The total of 373 specimens obtained comprised 102 climbing perch (Anabas testudineus), 74 three-spot cichlids (Cichlasoma trimaculatum), 84 Nile tilapia (Oreochromis niloticus), and 113 striped snakeheads (Channa striata). The prevalence, mean intensity and abundance of A. indicus were highest in C. striata with a prevalence of 81%, mean intensity of 5.17 parasites/fish and abundance of 4.06 parasites/fish. The lowest parasite infection level was seen in C. trimaculatum with a prevalence of 4.1%, mean intensity 1.66 and mean abundance of 0.06. Histological analysis showed inflammatory responses in the skin of snakeheads (hemorrhage, increased spread of melanomacrophage and leukocyte cells), melanomacrophage and the spread of leukocyte cells were observed in climbing perch. In contrast, melanomacrophage was often observed in tilapia and trimac cichlid. Blood imaging analysis showed significant differences (P <0.05) in the number of leukocytes and percentage of monocyte cells between uninfested fish and those infested with A. indicus.